Hepatic Histology in Treatment-naïve Children With Chronic Hepatitis B Infection Living in the United States and Canada. Issue 1 (July 2020) - Rodriguez-Baez, Norberto; Murray, Karen F.; Kleiner, David E.; Ling, Simon C.; Rosenthal, Philip; Carlin, Kristen; Cooper, Kara; Schwarz, Kathleen B.; Schwarzenberg, Sarah J.; Teckman, Jeffrey H.; Ghany, Marc G.; Alawad, Ahmad Samer
ABSTRACT: Objectives: Chronic hepatitis B virus infection is a major cause of morbidity and mortality. The aim of the study is to describe the hepatic histology in children chronically infected with hepatitis B virus living in the United States and Canada. Methods: Liver biopsies of 134 treatment-naïve children with chronic hepatitis B virus infection were scored for inflammation, fibrosis, and other histological features, and correlated with clinical and laboratory data. Results: Sixty percentage of subjects acquired the infection vertically, 51% were male, and 69% were hepatitis B e antigen-positive at the time of the biopsy. Hepatitis B DNA levels were generally high (mean 7.70 log IU/mL), as was serum alanine aminotransferase (median 120 U/L). Using the Ishak-modified histology activity index scoring system, interface hepatitis was mild in 31%, moderate in 61%, and severe in 6%. Lobular inflammation was mild in 54%, moderate in 29%, and marked in 7%. Portal inflammation was mild in 38% and moderate in 62% of subjects. Eighteen percentage had no fibrosis, 59% had portal expansion without bridging fibrosis, 19% had bridging fibrosis, and 4% had cirrhosis. Alanine aminotransferase positively correlated with inflammation and fibrosis. Neither age, duration of infection, nor Hepatitis B virus DNA levels correlated with fibrosis. Fibrosis-4 index did not correlate with fibrosis but correlated with inflammation. Aspartate aminotransferase/platelet ratio index correlated with both inflammation and fibrosis. Conclusions: Chronic hepatitis B virus infection results in significant inflammation and fibrosis during childhood. Serum alanine aminotransferase is a strong indicator of the severity and extent of hepatic inflammation and fibrosis. Abstract : Supplemental Digital Content is available in the text